Basic concepts in sociology - Weber, Max (Beacon Press, 1993)
Sociology of religion is the study of the beliefs, practices and organizational forms of religion using the tools and methods of the discipline of sociology. This objective investigation may include the use of both quantitative methods (surveys, polls, demographic and census analysis) and qualitative approaches such as participant observation, interviewing, and analysis of archival, historical and documentary materials.